USE OF THE 1-WIRE PROTOCOL IN SMART HOME COMPUTER SYSTEMS - STATSENKO, Dmytro; STATSENKO, Volodymyr; ROMANIUK, Yevheniia; OSYPENKO, Volodymyr (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The article examines the computer systems used in the "Smart House". A comparative analysis of these computer systems was carried out. It was emphasized that such systems have a number of advantages that have a positive impact on human life and safety. The use of temperature measuring devices is widely used in computer systems to monitor Smart Home conditions. The need to install a large number of sensors leads to an increase in the complexity of such computer systems. Protocols for connecting sensors to a microcontroller play an important role in system development. The analysis of the latest publications and studies provides information on the widespread use of the 1-Wire protocol in various fields to solve practical problems and the need for further improvement of systems using this protocol. Two simulation models of "Smart House" computer systems for determining indoor temperature based on the classic connection protocol and using the 1-Wire protocol are presented. The simulation model based on the standard protocol uses: an Arduino Uno board based on an Atmega328p microcontroller, LM35 temperature sensors and a 74HC4051D multiplexer. In the simulation model using the 1-Wire protocol, the following are used: Arduino Uno board and DS18B20 digital temperature sensors. Information is given on the operation of the 1-Wire protocol, which is widely used to connect a large number of sensors with such an interface, namely, there is a theoretical possibility of addressing an unlimited number of similar devices on a single-wire line. In the simulation model of the system with the used 1-Wire protocol, the number of sensors connected to one output is increased to 12 in order to analyze and demonstrate the capabilities of the system. According to the simulation results, the following parameters are presented: the number of possible connections, the complexity of the design, the use of compact software code, the frequency of the clock signal, and the cost of the Smart Home computer systems. The results of the analysis of the considered simulation models of computer systems are presented in the conclusions. Advantages and disadvantages of systems with 1-Wire protocol are given.